The Clinical Spectrum of Aspergillus Associated Infection in Humans: A Diagnostic and Management Approach - Choudhary, Pooja; Chhillar, Anil K. (Anti-Infective Agents, 2026)
Aspergillus is an opportunistic fungus and most common mould, both cosmopolitan and ubiquitous in nature, that causes life-threatening invasive aspergillosis and other grave infections, which pose a precise risk to patients with compromised immune systems. Despite improved therapeutic and diagnostic approaches, invasive aspergillosis remains a catastrophic fungal infection, such as COVID-19-associated pulmonary aspergillosis and influenza-associated pulmonary aspergillosis had a high prevalence in critically ill patients. It infects approximately ten million people each year, with a significantly high mortality rate. It is frequently convoluted COVID-19 and severe influenza disease by continuously challenging diagnostic and therapeutic strategies and concomitant with significant morbidity and mortality rates. However, Azole-resistant Aspergillus strains are rapidly emerging and creating a significant challenge in managing Aspergillus-associated infections. Promising new antifungal agents, including olorofim, fosmanogepix, ibrexafungerp, opelconazole, and rezafungin, are currently in clinical and preclinical trials. Treating conditions such as invasive aspergillosis, infections caused by resistant species, and those complicated by drug-drug interactions remains particularly difficult in clinical practice, highlighting the urgent need for alternative therapeutic strategies. In this review article, we highlight the characteristics and habitats of Aspergillus species, their pathogenicity, and the clinical challenges they pose, including diagnostic complexities. It also highlights existing and emerging therapeutic approaches for managing Aspergillus-associated infections. By integrating insights into the biology, diagnosis, and treatment of these infections, the review emphasizes the importance of innovative strategies to overcome current obstacles in clinical management.
Keywords: olorofim